Population structure and dynamic characteristics of Taxus cuspidata in Baishilazi National Nature Reserve, China - Baoliang Chang; Shuai Yu; Wei Chen; Xingyuan He; Yanqing Huang; Yue Zhang (Global Ecology and Conservation, 2024)
Taxus cuspidata is listed as a first-class national key protected plant in the northeast region, with scarce individuals in the wild and significant conservation value. We conducted a systematic field survey to explore the population structure and dynamic characteristics of T. cuspidata in the Baishilazi National Nature Reserve. A total of 313 T. cuspidata were recorded, displaying a spatially clustered distribution. Young individuals made up 33 % of the population, and the population's diameter class structure indicated a decreasing trend in population size. The population's survival curve closely resembled the Deevey-II type. These results suggest that the proportion of young individuals and strong potential for self-renewal. Geographic analysis revealed that north-facing slopes with moderate gradients were the primary habitat for T. cuspidata in the reserve. Interspecific analysis identified Acer ukurunduense and A. komarovii as the species with the highest interspecific associations with T. cuspidata. The population is projected to continue growing. The nature reserve is effectively fostering the natural renewal and recovery of T. cuspidata populations. These findings offer valuable insights for the conservation management of T. cuspidata in Baishilazi National Nature Reserve, supporting the sustainable development of endangered species populations.